The Impact of COVID-19 Cases on Stock Prices of Selected Companies Representing Tourism and Banking Sectors - Volkan Dayan; Monika Bolek; Juan E. Trinidad-Segovia (Finanse i Prawo Finansowe, 2023)
The purpose of the article/hypothesis: The purpose of the article is to analyse the relationship between stock prices of selected companies and COVID-19 cases in those countries where the tourism and banking sectors have a high share of national income, such as Croatia, Italy and Spain.